Promoción y reestructuración administrativa del complejo recreacional - deportivo "johavey" en puerto inca parroquia jesús maría - Ayala Roque, Patricia Margarita (2009)
The Canton Naranjal has few sport complexes even though you can findthen they don´t give a good service that they offer to customers don´t satisfy their needs.